2005
DOI: 10.1088/0957-4484/16/11/006
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical synthesis of single-crystalline CeOHCO3rods and their thermal conversion to CeO2rods

Abstract: Single-crystalline CeOHCO 3 rods with an orthorhombic structure have been successfully synthesized by the sonochemical method from aqueous solution containing CeCl 3 and urea. Polycrystalline CeO 2 rods have been prepared by thermal conversion of single-crystalline CeOHCO 3 rods at 500 • C in air. CeOHCO 3 and CeO 2 rods were characterized by x-ray powder diffraction (XRD), transmission electron microscopy (TEM), thermogravimetric analysis (TG) and differential scanning calorimetric analysis (DSC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 37 publications
1
55
0
Order By: Relevance
“…Urea is used to gradually raise the pH value of the reaction mixture, because on heating above 60 • C it undergoes hydrolysis and releases a small quantity of CO 3 2− and OH − . Syntheses of rare-earth compounds through urea decomposition have received considerable attention over the past several years [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Urea is used to gradually raise the pH value of the reaction mixture, because on heating above 60 • C it undergoes hydrolysis and releases a small quantity of CO 3 2− and OH − . Syntheses of rare-earth compounds through urea decomposition have received considerable attention over the past several years [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Lykhach [13,14] also found that CeO 2 activation led to the rapid formation of carbonate and surface carboxylates. Meanwhile, various 1D and 2D CeO 2 nanostructures, [15][16][17] including nanorods, [18] nanowires, [19] nanotubes, [20,21] nanobelts [22,23] and other morphologies [24][25][26][27][28] had been synthesized via the thermal decomposition of CeCO 3 OH precursors, which was often prepared by solution precipitation, [29] sol-gel, [30] microemulsion, [31] sonochemical, [32] hydrothermal methods. [33] However, these synthetic processes usually were complicated with high synthesis cost due to the expensive templates and additives.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have been published about doped CeO 2 with various cationsdopants, such as Ca, Al, Zr, Nd, Pb, Mn, Mg, Cu, Zn, Co, Y, Ba and Sr [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Literature survey shows that nanocrystalline ceria have been prepared by means of a variety of methods such as sol-gel process [29], hydrothermal or solvothermal synthesis [30,31], micro-emulsion [32], co-precipitation [33,34], conventional solid state method, flow method [35], microwave hydrothermal method [36], sonochemical synthesis [37], thermal decomposition [38], spray pyrolysis [39] etc. These methods operate mainly on high pressure, salt-solvent mediated high temperature or surface capping agent and the sizes of ceria particles are relatively large.…”
Section: Introductionmentioning
confidence: 99%